Impacts of the COVID-19 pandemic on the relationship between the economic factors and stock prices of the transport sector in the stock exchange of Thailand - Sirimat, Sukanya; Watchalaanun, Tanawat; Choochote, Kitimaporn; Nonthapot, Sakkarin (Asian Economic and Financial Review, 2023)
The COVID-19 pandemic has affected economic sectors and investment and has particularly affected the stock pricing factors for the transport sector (TRANS). This study compares the relationship of the different factors, i.e., the volume, exchange rate (EXR), consumer price index (CPI), and the oil price on the stock prices of the TRANS on the Stock Exchange of Thailand (SET) between the pre-COVID-19 and during COVID-19 periods. Time series data between January 2017 and December 2019 were used for the pre-COVID-19 period, and data between January 2020 and September 2022 were used for the during COVID-19 period. The effects of the independent variables were considered by estimating the long-run relationship using the autoregressive distributed lag (ARDL) and Granger causality from those variables to each stock price. The results found that the COVID-19 pandemic caused different effects on the volume, EX, CPI, and the oil price on the stock prices of the transport sector in the SET. Thus, investors should closely monitor the situations caused by natural disasters and the change of the EXR and oil price to reduce any problems that may arise.